Comparison of grain particle size distribution in the single kernel characterisation system and during first break roller milling - Muhamad, Ida Idayu; Fang, Chaoying; Campell, Grant M. (Penerbit UTM Press, 2006)
Flour milling has evolved into an efficient operation; however, process modelling, simulation, and optimisation can make significant improvements to the operation. A challenge of single kernel testing using an instrument such as the Perten Single Kernel Characterisation System (SKCS) is to relate the results to actual breakage achieved during roller milling. As a step toward this, wheat varieties covering a wide hardness range were broken in the SKCS and in the Satake STR–100 test roller mill (roll gaps of 0.3 – 0.8 mm; sharp–to–sharp and dull–to–dull roll dispositions) and the resulting breakage materials were studied for the two systems. The particle size distribution (psd) produced on breakage of wheat by the SKCS itself was measured using laboratory scale plansifting, and compared with the psd produced from first break milling at different roll gaps and under different roll dispositions. Under both sharp–to–sharp and dull–to–dull milling in the roller mill, the effect of increasing kernel hardness was due to the increase in the average size of the broken particles which showed that harder kernels do not break so readily. However, milling under dull–to–dull disposition at larger roll gaps showed the average psd decreased slightly with increasing kernel hardness. This unexpected result was also observed from the SKCS. Harder kernels resulted in smaller particles in the broken material which indicates a very positive crushing action within the SKCS. The psd from the SKCS was most similar to that produced from the roller mill at a roll gap of 0.8 mm under a dull–todull disposition